Mengukur Budaya Keselamatan Pasien di Rumah Sakit Umum Universitas Muhammadiyah Malang Menggunakan Menggunakan Survei HSOPSC - Wirasasmita Paripih; Tri Martiana; Inge Dhamanti (FORIKES, 2023)
Safety culture is a multidimensional concept as a product of values, attitudes, perceptions, competencies and behavioral standards of individuals and groups that determine commitment, style and administrative skills in managing patient safety. If this culture is strong, it will benefit the hospital. This study aimed to determine the dimensions of patient safety culture that need to be strengthened, so that it can be used as a tool for management and policy makers to encourage the improvement of a strong patient safety culture at the University of Muhammadiyah Malang General Hospital. The sampling technique in this study was convenient sampling so that 138 respondents were obtained including doctors, nurses and non-clinical employees. Measurements were made using the Hospital Survey on Patient Safety Culture (HSOPSC) version 2.0 questionnaire to measure 12 dimensions of patient safety culture in health workers at the General Hospital of the University of Muhammadiyah Malang. Data were analyzed descriptively. The results showed that the overall average positive response rate for the 12 patient safety culture dimensions of HSOPSC was 71.4%. The results of this study indicated that employees feel positive about the patient safety culture in their organization. The highest dimension with the highest positive response rate was “organizational learning - continuous improvement” while the lowest dimension was “reporting and handover - information exchange”. It was concluded that in general, the staff at the General Hospital of the University of Muhammadiyah Malang felt positive about the patient safety culture in their organization. It is recommended to evaluate and improve the dimensions of reporting and handover - exchange of information at the General Hospital of the University of Muhammadiyah Malang.Keywords: hospital; patient safety culture; HSOPSC questionnaire; dimensions ABSTRAK Budaya keselamatan merupakan konsep multidimensi sebagai produk dari nilai, sikap, persepsi, kompetensi dan standar perilaku individu serta kelompok yang menentukan komitmen, gaya dan kecakapan administrasi dalam mengelola keselamatan pasien. Apabila budaya ini kuat, maka akan menguntungkan rumah sakit. Penelitian ini bertujuan untuk mengetahui dimensi budaya keselamatan pasien yang perlu dilakukan penguatan, agar dapat digunakan sebagai alat bagi manajemen dan pembuat kebijakan guna mendorong peningkatan budaya keselamatan pasien yang kuat di Rumah Sakit Umum Universitas Muhammadiyah Malang. Teknik pengambilan sampel pada penelitian ini adalah convenient sampling sehingga didapatkan 138 orang responden termasuk dokter, perawat, dan karyawan non klinis. Pengukuran dilakukan menggunakan kuesioner Hospital Survey on Patient Safety Culture (HSOPSC) versi 2.0 untuk mengukur 12 dimensi budaya keselamatan pasien pada tenaga kesehatan di Rumah Sakit Umum Universitas Muhammadiyah Malang. Data dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa tingkat respon positif rata-rata keseluruhan untuk 12 dimensi budaya keselamatan pasien dari HSOPSC ini adalah 71,4%. Hasil penelitian ini menunjukan bahwa karyawan merasa positif terhadap budaya keselamatan pasien di organisasinya. Dimensi tertinggi dengan tingkat respon positif tertinggi adalah “pembelajaran organisasi - peningkatan berkelanjutan” sedangkan dimensi terendah adalah “pelaporan dan serah terima - pertukaran informasi”. Disimpulkan bahwa secara umum, staf di Rumah Sakit Umum Universitas Muhammadiyah Malang merasa positif terhadap budaya keselamatan pasien dalam organisasinya. Disarankan evaluasi dan peningkatan dimensi pelaporan dan serah terima - pertukaran informasi di Rumah Sakit Umum Universitas Muhammadiyah Malang.Kata kunci: rumah sakit; budaya keselamatan pasien; kuesioner HSOPSC; dimensi